Printing powerful powders: evaluating static and dynamic behaviour - Zyga, Jowita; McGee, Christine; Humphreys, Lisa; Stennett, Christopher (Cranfield University Defence and Security, 2024)
Additive Manufacturing (AM), commonly referred to as 3D printing, is a promising manufacturing technique, enabling near full control of the final product’s properties. With its unique approach to complex objects manufacturing, AM is investigated for its suitability of manufacturing with a wider range of materials. Despite the global research on AM of Energetic Materials that has already been conducted, final energetic devices often offer poorer product performance, compared to traditional manufacturing techniques. Reasoning for poorer outcomes could be attributed to the need for adapting and modifying Energetic Materials for AM purposes. To make the materials suitable for AM, there is a need for material modification, such as mixing energetic ingredient with solvent or binder, both of which often result in reducing the desirable outcome: the use of solvent can lead to uneven drying and shrinkage (and therefore producing voids within the product); too much binder is often responsible for low energetic density, therefore causing high burn rates and detonation velocities to be inaccessible. To overcome that, it would be beneficial to use raw, unmodified Energetic Materials – in their powdered form. Research conducted at Cranfield University, using Dry Powder Additive Manufacturing has proven, that energetic devices can be successfully printed using energetic powders. However, working with powders is often challenging: a lack of continuous flow, powder caking or powder-dispensing nozzle blockages are often experienced. To maximise the final product performance and avoid above issues, it is necessary to understand powder behaviour: its dynamic flow, bulk, shear and process properties. A deep understanding of those properties and their effect on manufacturing process is a crucial step to further developing this AM technique. Current methods of powder characterisation are typically limited to determination of 3 parameters: Angle of Repose, Carr (Compressibility) Index and Hausner Ratio. Scientific community have, however, proven these methods to be unreliable, proposing more thorough ways of powder studies: powder rheometers. Despite their growing popularity, analysis and interpretation of test results can still pose some challenges. Current research focuses on gaining better understanding of powder rheology and recognising how investigated powders’ properties translate to their behaviour during the printing process.
Keywords: Powder flowability; powder rheology; powder properties; powder Additive Manufacturing; Additive Manufacturing of energetic materials; 3D Printing of energetic materials